Vector Sensor Array Processing for Polarized Sources Using a Quadrilinear Representation of the Data Covariance - Miron, Sebastian (IntechOpen, 2010)
Vector Sensor Array Processing for Polarized Sources Using a Quadrilinear Representation of the Data Covariance